Towards inclusive global collaborations in coral reef science - Cassandra Roch; Shannon G. Klein; Carlos Angulo-Preckler; Andreas A. Hutahaean; Joshua Wambugu; Anaurora Yranzo-Duque; Taiba Alamoudi; Aya Naseem; Patricia González-Díaz; Narriman Jiddawi; Naira Pluma; Bashaer Algethami; et al. (npj Ocean Sustainability)
Abstract Protecting and restoring coral reefs demands concerted global efforts that transcend national boundaries. However, equitable participation in coral reef science remains challenging, particularly for researchers from lower-income nations. Through quantitative scientometric analyses and qualitative surveys, we examined global collaboration dynamics in coral reef research. Our findings reveal that high-income countries dominate the research landscape, often sidelining contributions from lower-income regions. While international collaborations were valued for benefits like access to funding, opportunities for professional development, enhanced publication success and improved conservation outcomes, most partnerships were short-term, with limited opportunities for evolving roles. Researchers from developing nations face significant barriers, including undervaluation of contributions, differing expectations around authorship, and ethical concerns like parachute science and tokenism, raising concerns about inclusivity and respect for local expertise. To improve collaborative practices and increase participation in coral reef science we propose actionable recommendations directed towards publishers, funders and the greater coral reef research community. We recommend fostering mutual respect, building long-term relationships, and promoting fair funding and publishing practices. These steps are essential for equitable research collaborations that support coral reefs and the communities that depend on them.